Sharp foreign bodies in the small bowel: Trial by fire - Kumar, N Pritesh; Bains, Lovenish; Lal, Pawan; Yasir Beg, Mohd.; Maranna, Haraesh (Indian Journal of Case Reports, 2020)
Foreign body ingestion is seen in both adults and children, either accidental or intentional. These may be blunt or sharp, either single or multiple. Most objects are eliminated in stools, but some cause complications. Endoscopy can retrieve foreign objects from the upper gastrointestinal tract, and colon, but retrieval of foreign objects in the small bowel, especially sharp objects, is challenging. In our case series, ingestion was accidental in one patient and intentional in three. The cases were evaluated clinically to look for signs of complications. X-rays done at the time of presentation confirmed the presence of sharp foreign object(s) in the gut. Each case was managed conservatively, without surgical or endoscopic intervention. Psychiatry consultation was sought for those who had swallowed the objects with intent. Management depends on various factors, the location being an important determinant of the plan of action. Gaining access to objects in the small intestine is a challenge. Complicated cases may require surgery. For objects within the small bowel, in the absence of complications, expectant management can be followed.